Kualitas Pelayanan Terhadap Keputusan Nasabah Tabungan Batara Pada Bank - Arjun, Muhammad; Agustian, Efandri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the quality of services provided to batara savings customers at PT. Jambi Bank Tabungan Negara (Persero) branch, then to find out the customer's decision on Batara Savings to save at PT. The Jambi State Savings Bank (Persero) Branch, and to find out the effect of service quality on customers' decisions on Batara Savings to save at PT. Bank Tabungan Negara (Persero) Jambi Branch. The method used by the author in this study is a survey method that is an investigation that is held to obtain the facts of the symptoms that exist and look for information - information factually, both about the social, economic or political institutions of a group or region. Survey research is used with the intention of explanation (explanatory) that there is data collected, processed and analyzed to be able to explain causal relationships or correlations between hypothesis testing variables. The analytical tool used in this study uses simple regression with proof of the hypothesis by statistical tests t. The results of the study show that service quality has a significant effect on customer decisions which are indicated by t count> t table and prog. sig <alpha (0.05). while the correlation value of 0.991 means that there is a close relationship between service quality variables and customer decision variables.